O princípio da vedação do retrocesso como instrumento de autovinculação do STF: proteção da presunção de inocência das pessoas acusadas no processo penal - Martini, João Henrique Imperia (2022)
This research has as its theme the principle of the principle of prohibition of setback and, as an objective, its application to the Judiciary, more specifically to the Supreme Federal Court, as a way of strengthening self-binding to its precedents that, at some point, represented advances in the protection of fundamental rights and guarantees of vulnerable and/or minority groups, more specifically in the case of the principle of presumption of innocence, protecting accused persons in criminal proceedings and preventing the provisional execution of the sentence from the second degree of criminal jurisdiction. The choice of theme arose from the observation, in recent years, of the jurisprudential changes that occurred within the STF in relation to the principle of presumption of innocence, without there being greater concern with objective criteria strengthened to overruling the precedent that, in 2009, represented the broader protection of that fundamental guarantee. The simple change in the composition of the Court was enough to, in 2016, after only seven years of the emancipatory decision, retreat in relation to the fundamental guarantee of the presumption of innocence. This observation also raised concerns about the stability of any precedents of the STF in terms of fundamental rights held by vulnerable and/or minority groups, especially considering the political instability experienced in Brazil, at least in the last ten years, resulting from the extreme political polarization within society, and the growing populist criminal movements, circumstances that can contribute to the erosion of the country's democratic foundations. Finally, it is a bibliographic review research, with a case study. At first, the theoretical and jurisprudential aspects of the principle of prohibition of setback were analyzed, moving on, then, to the study of the expansion of the constitutional jurisdiction of the STF and the formation of binding precedents with a true nature of a source of Law, to, at the same time, finally, to suggest a stronger model for overruling binding precedents when referring to fundamental rights and guarantees of vulnerable and/or minority groups, as in the case of the presumption of innocence of persons accused in criminal proceedings. The conclusion is that the principle of prohibition of setback is a valid legal basis to support the self-binding of the Supreme Federal Court (STF) in relation to its precedents that, at some point, advanced in the protection of the fundamental rights of those groups of people